Pengaruh Latihan Menggunakan Samsak terhadap Peningkatan Hasil Tendangan Ushiro Mawashi Geri pada Kegiatan Ekstrakulikuler Karate SMPN 1 Cikampek - Yosua Fernando Gultom; Setio Nugroho; Ardawi Sumarno (Departement of Mathematics Education, 2023)
This study aims to determine the Effect of Training Using Samsak on Increasing Ushiro Mawashi Geri's Kick Results in Karate Extracurricular Activities at SMPN 1 Cikampek. The subjects of this study were students of SMPN 1 Cikampek who participated in extracurricular Karate activities. The sample in this study was 15 people using total sampling. With 10 meetings 2 in between pretest and pretest to measure the initial test and the final test. In conducting the initial test, you can get a pretest score with a total score of 77 and a posttest with a total score of 199. The results of this study showed that the effect of training using samsak on the increase in the result of ushiro mawashi geri kicks managed to increase with the t-count produced was 10,693 and the t-table was 2,114. The results resulted in that the t-count value of the t-table > and significant probility was less than 0.05. So it can be concluded that there is a noticeable difference between the results of the Effect of Training Using Samsak on the Improvement of Ushiro Mawashi Geri's Kick Results on the pretest and posttest data. So that the influence of training using samsak has a significant impact on increasing the results of ushiro mawashi geri kicks on extracurricular participants of SMPN 1 Cikampek.